Preliminary study towards eco-design of housing in coastal settlements in Surabaya (Case study of fishermen housing design after the development of Kenjeran Bridge, Surabaya) - Dewi Septanti; Rika Kisnarini; Purwanita Setijanti; Ayi Syaeful Bahri; Wahyu Setyawana (Institut Teknologi Sepuluh Nopember, 2017)
This paper involves a discourse about design based research and the research itself. To capture the goals, the issues of this paper are how to re-design the housing surrounding the bridge which built for tourism reason ecologically. In order to improve the quality of the area surrounding the bridge and due to support the tourism and human life, this study would like to investigate the issues about the improvement of settlements quality related to their impact of post construction of the bridge. The study focused on the households’ requirements for functionality of houses especially to support tourism and business activities at home. Although several studies on coastal housing problems have been conducted widely, investigation on sustainability of the building is still limited (Kobayashi, 2000; Marfa’i, M.A, 2008). In term of method, this study was design as an explorative, descriptive, ex-poste and evaluation study. By using the in- depth interviews method, the idea, hope, expectation of inhabitants was gained. 30 respondents were taken from 3 local sub district area. The results showed that the households’ needs can be observed through their activities. Households’ activities determine their requirements for the houses design. The kind of activities also influence the houses design and it’s attributes (e.g size, the type of space). By comparing the attributes of the houses and households’ requirements, the design is determined. In which kinds of tourism activities are included in their daily activities.